Topological origin of the type-II Dirac fermions in PtSe2 - Li, Yiwei; Xia, Yunyouyou; Ekahana, Sandy Adhitia; Kumar, Nitesh; Jiang, Juan; Yang, Lexian; Chen, Cheng; Liu, Chaoxing; Yan, Binghai; Felser, Claudia; Li, Gang; Liu, Zhongkai; et al. (Physical Review Materials, 2017)
Group VIII transition-metal dichalcogenides have recently been proposed to host type-II Dirac fermions. They are Lorentz-violating quasiparticles marked by a strongly tilted conic dispersion along a certain momentum direction and therefore have no analogs in the standard model. Using high-resolution angle-resolved photoemission spectroscopy, we systematically studied the electronic structure of PtSe2 in the full three-dimensional Brillouin zone. As predicted, a pair of type-II Dirac crossings is experimentally confirmed along the kz axis. Interestingly, we observed conic surface states around time-reversal-invariant momenta Γ and M points. The signatures of nontrivial topology are confirmed by the first-principles calculation, which shows an intricate parity inversion of bulk states. Our discoveries not only contribute to a better understanding of topological band structure in PtSe2 but also help further explore the exotic properties, as well as potential application, of group VIII transition-metal dichalcogenides.
CRIS-Team Scopus Importer:2022-04-14